A novel prognostic score of recurrence for endometrial cancer patients with staging surgery - Tomoka Maehana; Naoki Kawahara; Junya Kamibayashi; Motoki Matsuoka; Keita Waki; Ryuji Kawaguchi; Fuminori Kimura (BMC Women's Health)
Abstract Background Recently, there have been an increasing number of reports on the association between inflammatory markers and the prognosis of malignant tumors. However, the current inflammatory indicators have limited accuracy. We aimed to develop a new scoring system for predicting endometrial cancer recurrence using inflammatory markers, tumor markers, and histological diagnoses. Methods Patients with primary, previously untreated, and suspected endometrial cancer who underwent surgery at the Nara Medical University Hospital between January 2007 and December 2020 were included and followed up until March 2024. Items were divided into positive and negative using scores based on cutoff values and placed into the new scoring system, the endometrial tumor-related (ETR) score. Results We found that positive postoperative histological examination of lymph node metastasis and myometrial invasion, high levels of carcinoembryonic antigen and D-dimer in preoperative blood tests, and a large difference in preoperative and postoperative white blood cell counts were significantly associated with recurrence. The sensitivity and specificity of recurrence prediction using the ETR score were not inferior to those using the International Federation of Gynecology and Obstetrics staging system, which is considered the best prognostic factor for survival. Conclusions The ETR score is a significant prognostic marker of recurrence in patients who have undergone staging surgery, with complete surgical tumor removal.